THE USE OF VIDEO CONVERSATION IN TEACHING SPEAKING AT SMP NEGERI 6 PONTIANAK - Susanti, .; ., H.Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : This reasearch focus on the use video conversation in teaching speaking at seventh grade students in SMP Negeri 6 Pontianak in academic years 2014/2015. This research raise because the researcher interested to described how a English teacher teaching by using video conversation. The researcher used descriptive qualitative research with direct and indirect data as teachnique of data collecting. The reseacher conducted interview, participant observation and documentation as tool of data collecting. The research results show that it was more efective using video conversation in teaching speaking at SMP Negeri 6 Pontianak. The students were easier to understand what the teacher teach and explain. The students more interest and active in the class. The teacher provided materials based on texts, such as textbooks and LKS (Lembar Kerja Siswa) and the teacher searching the videos appropiate with the material in internet. In addition, the teacher provided the students with assessment that emphasizes the measurement of learning outcomes in the form of students’ competencies to do something. Keywords : Video conversation, Teaching speaking Abstrak : Penelitian ini fokus pada penggunaan vidio percakapan didalam mengajar berbicara pada siswa SMP Negeri 6 pontianak kelas 7 tahun akademik 2014/2015. Penelitian ini diangkat karena peneliti tertarik untuk mendeskripsikan bagaimana seorang guru Bahasa Inggris mengajar menggunakan vidio percakapan. Peneliti menggunakan penelitian diskriptif kualitatif dengan teknik langsung dan tidak langsung sebagai teknik pengumpulan data. Peneliti melakukan wawancara, observasi peserta dan dokumentasi sebagai alat pengumpulan data. Hasil penelitian menunjukkan bahwa lebih efektif menggunakan vidio percakapan dalam mengajar berbicara di SMP Negeri 6 Pontianak. Siswa lebih mudah untuk mengerti apa yang guru ajarkan dan jelaskan. Siswa lebih tertarik dan aktif di dalam kelas. Guru menyediakan materi berdasarkan teks seperti buku-buku dan LKS (Lembar Kerja Siswa) dan guru mencari vidio yang sesuai dengan materi di internet. Sebagai tambahan, guru menyediakan penilaian siswa untuk mengukur hasil pembelajaran dalam bentuk kemampuan siswa melakukan sesuatu. Kata Kunci : Vidio percakapan, Mengajar berbicara